2007
DOI: 10.1159/000101730
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition and Reflexivity in Patients with Schizophrenia

Abstract: Background: Many patients with schizophrenia demonstrate a lack of insight into their disorder and often do not complain about their cognitive impairments. This might be due to generally reduced metacognitive abilities. Sampling and Methods: Twenty-seven patients with a DSM IV diagnosis of schizophrenia and 19 healthy control subjects performed 2 separate tasks tapping into metacognitive functions. In the first experiment the participants encoded words. In the following recognition part they judged their level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 41 publications
0
34
3
1
Order By: Relevance
“…So far, several studies have shown that patients with schizophrenia exhibit deficits in metacognition, i.e. the judgment of one’s own performance in a test [58,59]. However, the relationship between metacognition and ego disturbances has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies have shown that patients with schizophrenia exhibit deficits in metacognition, i.e. the judgment of one’s own performance in a test [58,59]. However, the relationship between metacognition and ego disturbances has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Thought disorder may be a multilevel disturbance involving abnormalities in thinking, language processing and social cognition, and 'communication disorder' may actually be more appropriate to describe this group of phenomenon [22] . A recent study showed that metacognitive faculties seem to be a separable cognitive entity, with patients with schizophrenia demonstrating impaired metacognitive capacities, independent of current symptoms or memory performance [23] .…”
Section: Discussionmentioning
confidence: 99%
“…So wurde vereinzelt eine generelle Über-konfidenz bei Psychose gefunden [Kircher et al, 2007]. Die Stärke der Konfidenz scheint von der subjektiven Kompetenz der Person und der Schwierigkeit einer Aufgabe abzuhängen.…”
Section: Empirische Fundierungunclassified